English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1. 5x-3y=-18
x -6y=-9

2. 3x-2y=12
2x+y=1

4. 4x-y= -14
3x+2y= -16

2007-01-09 14:51:57 · 4 answers · asked by Lx 1 in Science & Mathematics Mathematics

4 answers

Use Elimination Method.

Mulitply the second equation by 5 to match up the x's

5x - 3y = -18
5x - 30y = -45

Now subtract the equations and solve for y!

Once you have y ---sub it into one of the equations and solve for x.

Check that it works in the other equation and you are done!


Follow the same steps for theother ones.

2007-01-09 14:57:38 · answer #1 · answered by keely_66 3 · 0 0

i just learned this today, but i understand it. the first roblem you have to change the equation's direction
18=5x-3y
9=x-6y
then solve for x on the simplest one
9=x-6y so that simplifies to
9+6y=x
then substitute the 9+6y=x wherever there is an x in the equation, in this case it would look like this

5(9+6y)-3y=18
solve it
45+30y-3y=18
again
45+27y=18
27y=27
so y=1
then insert the y and solve for x
then do the same for the rest of the problems :D

2007-01-09 15:05:30 · answer #2 · answered by isabel 2 · 0 0

1. 5x-3y=-18 multiply both sides by -2
-10x+6y=36
x -6y=-9 add
-9x=27 divide both sides by -9
x=-3
5x-3y=-18 substitute x=-3
5(-3)-3y=-19
-15-3y=-18 add 15 to each side
-3y=-3 divide by -3
y=1
(-3, 1)

2. 3x-2y=12
2x+y=1 multiply both sides by 2
4x+2y=2
3x-2y=12 add
7x=14 divide b oth sides by 7
x=2
2x+y=1 substitute x=2
2*2+y=1 subtract 4 from each side
y=-3
(2, -3)

4. 4x-y= -14 multiply both sides by 2
8x-2y=-28
3x+2y= -16 add
11x=-44 divide both sides by 11
x=-4
4x-y= -14 substitute x=-4
4(-4)-y=-14
-16-y=-14 add 16 to each side
-y=2 divide both sides by -1
y=-2
(-4, -2)

2007-01-09 15:02:10 · answer #3 · answered by yupchagee 7 · 0 0

1.

x=9+6y

5(9+6y)-3y=-18
45+6y-3y=-18
6y-3y=-27
3y=-27
y=-9

x=9+6(-9)

x=-45

2007-01-09 15:00:32 · answer #4 · answered by Tiff 5 · 0 0

fedest.com, questions and answers